Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.2 - Inverse Functions - Exercise Set: 33

Answer

$f^{-1}$(x)=$x^{3}$

Work Step by Step

f(x)=$\sqrt[3] x$ y=$\sqrt[3] x$ x=$\sqrt[3] y$ $x^{3}$=y y=$x^{3}$ $f^{-1}$(x)=$x^{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.